Prevalence of myocarditis in pediatric intensive care unit cases presenting with other system involvement - Hanaa Ibrahim Rady; Hanan Zekri (Brazilian Society of Pediatrics, 2015)
Objective: To assess children with myocarditis, the frequency of various presenting symptoms, and the accuracy of different investigations in the diagnosis. Methods: This was an observational study of 63 patients admitted to PICU with non‐cardiac diagnosis. Cardiac enzymes, chest‐X ray, echocardiography, and electrocardiogram were performed to diagnose myocarditis among those patients. Results: There were 16 cases of definite myocarditis. The age distribution was non‐normal, with median of 5.5 months (3.25-21). Of the 16 patients who were diagnosed with myocarditis, 62.5% were originally diagnosed as having respiratory problems, and there were more females than males. Among the present cases, the accuracy of cardiac enzymes (cardiac troponin T [cTn] and creatine phosphokinase MB [CKMB]) in the diagnosis of myocarditis was only 63.5%, while the accuracy of low fractional shortening and of chest‐X ray cardiomegaly was 85.7 and 80.9%; respectively. Cardiac troponin folds 2.02 had positive predictive value of 100%, negative predictive value of 88.7%, specificity of 100%, sensitivity of 62.5%, and accuracy of 90.5%. Conclusions: Children with myocarditis present with symptoms that can be mistaken for other types of illnesses. When clinical suspicion of myocarditis exists, chest‐X ray and echocardiography are sufficient as screening tests. Cardiac troponins confirm the diagnosis in screened cases, with specificity of 100%.